Synthesis of NiO–Co3O4 nanosheet and its temperature-dependent supercapacitive behavior. (9th October 2018) - Saykar, Nilesh G; Pilania, Ritu Kumari; Banerjee, I; Mahapatra, S K
Abstract: A nanosheet of nickel and cobalt double hydroxides (NC RT) has been synthesized by the facile hydrothermal method. It has been treated at temperatures of 300 °C, 400 °C and 500 °C, namely NC 300, NC 400 and NC 500, respectively, to obtain a nanosheet of NiO–Co3 O4 . Samples have been investigated using XRD, Raman spectroscopy, FESEM and TEM. It can be observed that nickel hydroxide is converted to NiO at 300 °C, whereas cobalt hydroxide is converted to Co3 O4 at 400 °C. The double hydroxide nanosheet leads to porous oxide nanosheet at an elevated temperature. The formation of porous structure could be attributed to the rapid release of water molecules during thermal treatment. Four symmetric supercapacitors are prepared with NC RT, NC 300, NC 400 and NC 500 as electrode materials, keeping 3 M KOH as an electrolyte and Whatman filter paper as a separator for all the symmetric supercapacitors. It can be seen that the specific capacitances of the NC RT, NC 300, NC 400 and NC 500 symmetric supercapacitors are decreased with increasing temperature in the range of 25 °C–80 °C and scan rate in the range of 10–500 mV s −1 . It can be seen that the NC 300 has excellent supercapacitive behavior. The specific capacitance of NC RT decreased from 20 to 6 F g −1, NC 300 decreased from 324 to 57 F g −1, NC 400 decreased from 132 to 61 F g −1 and NC 500 decreased from 81 to 48 F g −1 with the variation of scan rate from 10–500 mV s −1 . The decrement in the specific capacitance may be attributed to the increased bulk and charge transfer resistance at elevated temperature.